UI/UX Design of a Student Deferment Application Using a User-Centered Design Approach - Prayogo, Ario Harry; Laily Indaryani; Elvira Lailatuth Thohiroh (Bahasa Indonesia, 2025)
The process for postponing tuition fee payments (Biaya Penyelenggaraan Pendidikan or BPP) serves as a facility for students who require a deferred payment arrangement. Currently, this process is still carried out manually, leading to issues such as delays, inconsistent data, and low process efficiency. This study aims to develop a BPP payment deferral application with a focus on user interface design, to support more efficient user-related processes. The interface was developed using the User-centered Design (UCD) method, which prioritizes user needs throughout the development process. The UCD approach includes the following stages: identifying the context of use, specifying user requirements, creating design solutions, and evaluating the design. The System Usability Scale (SUS) was employed to evaluate the usability level quantitatively. The evaluation resulted in a SUS score of 80.67, which falls into the ‘acceptable’ category and corresponds to a grade scale of ‘C’. These results indicate that the developed design meets user needs in terms of usability. The findings can serve as a foundation for the subsequent phase, namely the development of the full software system.